1992
DOI: 10.1557/proc-283-501
|View full text |Cite
|
Sign up to set email alerts
|

Microcrystalline Silicon by Dc Magnetron Sputtering: Growth Mechanisms

Abstract: We have used real-time, in situ spectroscopic ellipsometry (SE) and infrared reflectance (IR) to study microcrystalline silicon (ptc-Si) formation in reactive magnetron sputtering (RMS). g.c-Si growth occurs at high hydrogen partial pressures and moderate substrate temperatures. We use IR studies and SE studies of film growth on rough surfaces, respectively, to show that these conditions lead to high hydrogen coverage of the film surface and high effective surface diffusivity. The interface region is amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The dashed line is the total thickness increase for the two overlayers; it is fairly linear both before and after pc-Si:H layer formation, i.e., there is no observed difference in the deposition rates for these two phases. Feng et al, observed by single wavelength ellipsometry that the growth rate of the initial a-Si:H layer was higher than that of bulk pc-Si:H (Feng, et al, 1993). The difference may arise because the earlier study made no attempt to distinguish the contributions from H implantation and pc-Si:H deposition in fitting the real time trajectory.…”
Section: Sub-surface Transformation Of A-si:h To Pc-si:hmentioning
confidence: 98%
See 1 more Smart Citation
“…The dashed line is the total thickness increase for the two overlayers; it is fairly linear both before and after pc-Si:H layer formation, i.e., there is no observed difference in the deposition rates for these two phases. Feng et al, observed by single wavelength ellipsometry that the growth rate of the initial a-Si:H layer was higher than that of bulk pc-Si:H (Feng, et al, 1993). The difference may arise because the earlier study made no attempt to distinguish the contributions from H implantation and pc-Si:H deposition in fitting the real time trajectory.…”
Section: Sub-surface Transformation Of A-si:h To Pc-si:hmentioning
confidence: 98%
“…There is no evidence for the role of etching in this sub-surface phase transformation: if a-Si:H were etched away between the pc-Si:H nucleation sites, then we would expect larger values of void content in the yc-Si:H layer and a lower net growth rate; neither of these is observed. We previously observed with in situ IR absorption that a high H content in the nearsurface is associated with the nucleation of crystallites (Feng, et al, 1993). Here, the near-surface rapidly achieves a high, steady-state C, value, followed by p-Si:H nucleation, then a transformation of near-surface a-Si:H into pc-SkH and steady-state growth of pc-Si:H. In RMS, the pc-Si:H nucleation and growth process may be assisted by several forms of energy deposition in the film surface, including the translational energy of the sputtered Si, plasma ions, and fast H. (TE) to study the nature of the hydrogen bonding configurations and to measure the total hydrogen content of the films.…”
Section: Sub-surface Transformation Of A-si:h To Pc-si:hmentioning
confidence: 99%